Proof of Predicate Crime as a Basis for Prosecution of Money Laundering Crimes - Rika Kurniasari Abdulgani (GoAcademica Research & Publishing, 2022)
Money laundering is an act that is passed on from the original criminal act (follow-up crime). In Indonesia, the criminalization of money laundering is realized by Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering Crimes, which repeals Law Number 15 of 2002. Article 69 of Law Number 8 of 2010 explains that